Overview of Bearingless Induction Motors. (6th March 2014) - Sun, Xiaodong; Chen, Long; Yang, Zebin
Abstract : Bearingless induction motors combining functions of both torque generation and noncontact magnetic suspension together have attracted more and more attention in the past decades due to their definite advantages of compactness, simple structure, less maintenance, no wear particles, high rotational speed, and so forth. This paper overviews the key technologies of the bearingless induction motors, with emphasis on motor topologies, mathematical models, and control strategies. Particularly, in the control issues, the vector control, independent control, direct torque control, nonlinear decoupling control, sensorless control, and so forth are investigated. In addition, several possible development trends of the bearingless induction motors are also discussed.